Mixed triorganobismuthines RAr2Bi [Ar = C6F5, 2, 4, 6-(C6F5)3C6H2] and hypervalent racemic Bi-chiral diorganobismuth(iii) bromides RArBiBr (Ar = C6F5, Mes, Ph) with the ligand R = 2-(Me2NCH2)C6H4. Influences of the organic substituent. Issue 23 (26th February 2016) - Olaru, Marian; Nema, Mihai G.; Soran, Albert; Breunig, Hans J.; Silvestru, Cristian
Abstract : RAr2 Bi and chiral RArBiBr were structurally characterized; N–Bi bond distances in RArBiBr appear to be similar regardless of the electronic properties of the Ar ligand. Abstract : Triorganobismuthines R(C6 F5 )2 Bi (1 ) and R[2, 4, 6-(C6 F5 )3 C6 H2 ]2 Bi (2 ) [R = 2-(Me2 NCH2 )C6 H4 ] were synthesized by reaction of RBiBr2 with C6 F5 MgBr and 2, 4, 6-(C6 F5 )3 C6 H2 Li, respectively, in a 1 : 2 molar ratio. The Bi-chiral bromides R(C6 F5 )BiBr (3 ), R(Mes)BiBr (4 ), and R(Ph)BiBr (5 ) were obtained from RBiBr2 and C6 F5 MgBr, MesMgBr or PhMgBr, or from PhBiBr2 and RLi, in a 1 : 1 molar ratio. The molecular structures of1–5 were determined by single-crystal X-ray diffraction and are discussed taking into account the chirality of the species. Supramolecular aspects in the solid state are presented. The solution behaviour of the title compounds, including dynamic aspects, are discussed on the basis of multinuclear ( 1 H, 13 C, 19 F) NMR spectroscopy.